PENILAIAN MENOPAUSAL RATING SCALE (MRS) PADA WANITA MENOPAUSE DI KOTA PEMATANGSIANTAR TAHUN 2019 - Simangunsong, Dame Evalina (Poltekkes Kemenkes Medan, 2019)
Climacterium syndrome is a collection of symptoms experienced by a woman who started at the end of the reproductives until the five years after menopause. This time is a difficult time that women must be passed on with different complaints from each individual. The complaint can be categorized into four complaints such as physical complaints, vasomotor complaints, psychosocial complaints, urogenital complaints. Various complaints experienced can decrease the quality of life of women. Complaints experienced by menopause women can be assessed by Menopausal Rating Scale (MRS).This research is a descriptive type of research with a crosssectional design that aims to determine the description of menopausal complaints experienced by menopausal women in two locations in Pematangsiantar City. The results of the study illustrate that women who are examined in two research locations experience menopausal complaints in the weight category, especially in psychological and urogenital complaints. There is a health care effort in women before the menopause arrives. It is very important to prepare women in receiving the menopause and face the various complaints that will be experienced.